The Risk Management Balancing Act : Developed and Emerging Market Practices - International Finance Corporation (Washington, DC, 2015)
The purpose of the report is to present the findings from IFC’s recent survey on risk and nonperforming loan management practices in financial institutions together with supporting benchmarks and global trends in risk management. Top tier financial institutions in their respective markets have participated in the survey, including 25 SME focused banks and 2 microfinance institutions in 18 countries (see Exhibit 1). The emphasis on credit risk in this report stems from credit risk being the largest risk taken by SME focused banks. The report aims to help emerging market financial institutions that participated in the survey: Better understand the current state of their risk management capabilities in credit risk, loan portfolio monitoring and nonperforming loan management. Be able to compare their current risk management capabilities in these areas with peers in emerging and developed markets. Provide a basis for identifying key areas where their risk management can be enhanced going forward.